INSIGHT INTO THE MOLECULAR INTERACTION OF ANTI MALARIAL COMPOUNDS AS POTENTIAL CHORISMATE SYNTHASE INHIBITORS - s, SAJITHA LULU; a, THABITHA; A, MOHANA PRIYA; S, Vino (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The study is focused and directed towards a promising gateway for novel inhibitor designing against malaria. Methods: Homology model was built for both ON-state and OFF-state of Plasmodium falciparum chorismate synthase (PfCS) protein. Around 240 antimalarial compounds were docked into the active site of PfCS to understand the interaction and binding affinity. Virtual screening was carried out based on docking score, molecular properties, drug likeliness and bioactivity toward lead molecule selection. Results: Based on these properties out of 240 compounds, we found the best fit ligand idarubicin interacting with Arg46, Lys60, Glu86, Arg483 and Arg491 of ON state PfCS, with a high docking score of -13.7. The stability of complex and hydrogen bonds were analysed with molecular dynamic simulations. In OFF state also idarubicin interacting with a docking score of -15.2 and interacting residues was found to be Ser16, Glu86, Gly126, Arg127 and Arg491. Conclusion: Malaria, a cataclysmic disease caused by protozoan parasite P. falciparum is a leading disease and cause of death in many of the developing countries. CS is an enzyme, which plays a major role in the aromatic amino acid biosynthesis of the shikimate pathway. Inhibition of PfCS protein is reported to affect the growth and survival of the parasite. In this study, idarubicin compound shows anti-parasitic activity and high binding affinity towards PfCS. Keywords: Homology model, Drug likeliness, Shikimate pathway, Idarubicin.